(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The field of ecolinguistics has developed into a flourishing field of linguistics that is nearer than ever to the persistent matters in this period. It is believed that ecology, language and policies are three separate concepts. Due to this, the paper attempts to fill the gap by investigating two presidential statements in order to reveal the fundamental ideologies that govern environmental policies hidden in the language used. The data are selected from the statements of two presidents; Joe Biden (President of United States) and Cyril Ramphosa (President of South Africa) that are delivered in the conference of parties (COP 27), held in Sharm Al-Sheikh, 2022, about adopting environmental policies to combat the impact of climate change. The study that is qualitative in nature adopts two levels of analysis depending on Stibbe’s (2015) model of ecolinguistic analysis and van Dijk’s (2006) model of critical discourse analysis. The findings present two types of information; the cognitive level sets forth the economic terms that are repeated through the presidents’ statements to focus on the prominence of financial issues especially “private sector” and “investment” that are mentioned in various terms whereas, the ideological level reveals that one type of discourse is offered in those statements, which is ambivalent discourse. The study could be very useful to all scholars and others interested in environmental issues.